Intra‐ and inter‐cores fungal diversity suggests interconnection of different habitats in an Antarctic frozen lake (Boulder Clay, Northern Victoria Land). (30th June 2020) - Sannino, Ciro; Borruso, Luigimaria; Mezzasoma, Ambra; Battistel, Dario; Zucconi, Laura; Selbmann, Laura; Azzaro, Maurizio; Onofri, Silvano; Turchetti, Benedetta; Buzzini, Pietro; Guglielmin, Mauro
Summary: A perennially frozen lake at Boulder Clay site (Victoria Land, Antarctica), characterized by the presence of frost mounds, have been selected as an in situ model for ecological studies. Different samples of permafrost, glacier ice and brines have been studied as a unique habitat system. An additional sample of brines (collected in another frozen lake close to the previous one) was also considered. Alpha‐ and beta‐diversity of fungal communities showed both intra‐ and inter‐cores significant ( p < 0.05) differences, which suggest the presence of interconnection among the habitats. Therefore, the layers of frost mound and the deep glacier could be interconnected while the brines could probably be considered as an open habitat system not interconnected with each other. Moreover, the absence of similarity between the lake ice and the underlying permafrost suggested that the lake is perennially frozen based. The predominance of positive significant ( p < 0.05) co‐occurrences among some fungal taxa allowed to postulate the existence of an ecological equilibrium in the habitats systems. The positive significant ( p < 0.05) correlation between salt concentration, total organic carbon and pH, and some fungal taxa suggests that a few abiotic parameters could drive fungal diversity inside these ecological niches.